Factors affecting the level of medication adherence to anti-diabetic treatment: A multi- center cross-sectional study in Eastern Bhutan - Tashi Wangchuk; Phuntsho Norbu; Sherab Dorji; Sonam Tashi; Dorji Wangmo; Kinzang Wangdi; Tandin Wangay; Tshering Norbu (Bhutan Health Journal, 2024)
Background: Worldwide, Diabetes Mellitus affects millions of people. It is a chronic and progressive disease requiring a long-term treatment plan, adherence to which becomes extremely challenging. Globally, there is a poor level of medication adherence to anti-diabetic treatment and several studies have explored the factors affecting medication adherence. However, in Bhutan, there is limited data on the rate of medication adherence and factors affecting it. . Therefore, the study aimed to find the level of anti- diabetic medication adherence and factors affecting it.